2013
DOI: 10.1097/ccm.0b013e31828a3c13
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Maneuvers Modulate Epithelial and Endothelial Cell Response According to Acute Lung Injury Etiology*

Abstract: CPAP-30 worsened markers of potential epithelial cell damage in pulmonary acute lung injury, whereas both CPAP-30 and STEP-30/30 yielded endothelial injury in extrapulmonary acute lung injury. In both acute lung injury groups, recruitment maneuvers improved respiratory mechanics, but stepwise recruitment maneuver without sustained airway pressure appeared to associate with less biological impact on lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 27 publications
2
40
1
3
Order By: Relevance
“…A previous study has proposed to set PEEP according to the level of IAP in experimental ALI in pigs [19]. Another recent study has suggested that PEEP higher than IAP maintains functional residual capacity and prevents alveolar collapse [11]. In this line, in the present study, not even the highest PEEP value (10 cmH 2 O = 7.4 mmHg), which was lower than IAP (15 mmHg), was able to prevent alveolar collapse in our animals, independent of ALI etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has proposed to set PEEP according to the level of IAP in experimental ALI in pigs [19]. Another recent study has suggested that PEEP higher than IAP maintains functional residual capacity and prevents alveolar collapse [11]. In this line, in the present study, not even the highest PEEP value (10 cmH 2 O = 7.4 mmHg), which was lower than IAP (15 mmHg), was able to prevent alveolar collapse in our animals, independent of ALI etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Airflow, airway (P,aw) and esophageal pressures (Pes) were continuously recorded throughout the experiments with a computer running custom software written in LabVIEW® (National Instruments, Austin, TX, USA) [11]. V T was calculated by digital integration of the flow signal.…”
Section: Methodsmentioning
confidence: 99%
“…Gradual recruitment (step) maneuvers have been quite effective when applied to heterogeneous lung parenchyma, with different time constants for small airways opening, thus promoting lower biological impact when compared with the abrupt pressure increase 41 . The step can be obtained through a slow and gradual increase of PEEP or also by increasing inspiratory driving pressure up to a threshold pressure, in general 40cm H 2 O.…”
Section: Methods Methods Methods Methodsmentioning
confidence: 99%
“…The step can be obtained through a slow and gradual increase of PEEP or also by increasing inspiratory driving pressure up to a threshold pressure, in general 40cm H 2 O. Furthermore, in step there are smaller hemodynamic effects, since the average pressure achieved during this maneuver is lower 41 .…”
Section: Methods Methods Methods Methodsmentioning
confidence: 99%
“…27 Takođe, u eksperimentalnom, endotoksinom indukovanom ARDS-u, stepeničasti RM, u poređenju sa kontinuiranim pozitivnim pritiskom, dovodi do manjeg stepena oštećenja pneumocita tipa II (alveolarne ćelije koje produkuju plućni surfaktant) i smanjene ekspresije markera koji su udruženi sa nastankom fibroze i oštećenjem endotelnih ćelija u ARDS-u. 28 Posebna prednost stepeničastog (staircase) RM predstavlja mogućnost određivanja optimalne, individualizovane vrednosti PEEP-a za svakog bolesnika.…”
Section: Metode Izvođenja Rekrutment Manevaraunclassified